Development and application of an improved protocol to characterize biofilms in biologically active drinking water filters. Issue 2 (22nd December 2016) - Elhadidy, Ahmed M.; Van Dyke, Michele I.; Chen, Fei; Peldszus, Sigrid; Huck, Peter M.
Abstract : The objective was to develop and apply an improved, comprehensive biofilm characterization protocol for cellular and extracellular polymeric substances in drinking water biofilters. Abstract : Biofilms are central to the functioning of biologically active filters for drinking water production, and accurate biofilm characterization is crucial for elucidating biofiltration mechanisms and for identifying parameters indicative of biofilter performance. Drawing on recent findings in environmental engineering and microbiology, the objective was to develop and apply an improved, comprehensive biofilm characterization protocol to accurately measure the cellular and extracellular polymeric substance (EPS) composition in biofilms attached to drinking water biofilters. Key is the cation exchange resin extraction procedure, which was adapted and optimized to separate biofilm cells and EPS directly from the biofilter media while minimizing cell lysis. This step simplifies the overall procedure by combining biofilm detachment with biomass and EPS extraction steps and has not yet been applied to drinking water biofilters. Biomass was measured using both ATP and flow cytometry, and EPS composition was determined using spectrophotometric methods for total proteins and carbohydrates, and more advanced analytical techniques including fluorescence spectroscopy and liquid chromatography with organic carbon detection. This protocol was applied to pilot-scale biofilters, and the unique combination of characterization techniques allowed relationships among parameters to be identified. There were strong correlations between the cellular and EPS components and cellular ATP content, which had not been shown previously for drinking water biofilters. The EPS protein to carbohydrate ratio and the EPS C/N ratio were stable over the monitoring period. As well, nearly 50% of the biofilm EPS had a molecular weight larger than 2000 Da, composed of predominantly protein-like substances.